CRC handbook of chemistry and physics - Haynes, William M., editor; Lide, David R., 1928- editor; Bruno, Thomas J., editor (Boca Raton, Fla. : CRC ; London : Taylor & Francis [distributor], 2012)
Includes bibliographical references and index